Sudden death in racehorses: postmortem examination protocol. (July 2017) - Diab, Santiago S.; Poppenga, Robert; Uzal, Francisco A.
In racehorses, sudden death (SD) associated with exercise poses a serious risk to jockeys and adversely affects racehorse welfare and the public perception of horse racing. In a majority of cases of exercise-associated sudden death (EASD), there are no gross lesions to explain the cause of death, and an examination of the cardiovascular system and a toxicologic screen are warranted. Cases of EASD without gross lesions are often presumed to be sudden cardiac deaths (SCD). We describe an equine SD autopsy protocol, with emphasis on histologic examination of the heart ("cardiac histology protocol") and a description of the toxicologic screen performed in racehorses in California. By consistently utilizing this standardized autopsy and cardiac histology protocol, the results and conclusions from postmortem examinations will be easier to compare within and across institutions over time. The generation of consistent, reliable, and comparable multi-institutional data is essential to improving the understanding of the cause(s) and pathogenesis of equine SD, including EASD and SCD.